The combination effect of triamcinolone acetonide and tamoxifen citrate on fibroblast populated collagen lattice contractions - Agung Pranoto; Satiti Retno Pudjiati; Yohanes Widodo Wirohadidjojo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Keloid is caused by fibroblast hyperproliferation stimulated by transforming growth factor-IH ITGF-131 I, and it is usually treated with triamcinolone acetonide (TAl, which has the ability to inhibit TGF131 synthesis. However, the clinical results is still unsatisfied. Another drug that may inhibit keloid fibroblast TGF-131 synthesis is tamoxifen citrate (TCI, but the effect of the combination on keloid fibroblast activities has never been published.Objective: To find out the effect of combined triamcinolone acetonide and tamoxifen citrate on fibroblast keloid activities in vitro.Methods: It was a parallel post-test only study. The third passage keloid fibroblasts were isolated from a patient with keloid, cultivated in collagen lattice, and treated with several combinations of 5, 10, and 20 pM TA and 10, and 20 pM TC. Lattice contractions were measured based on digital image using scion image.Results: Among TA groups, the best inhibition of lattice contraction was found among 20 pM treated group and among TC groups. The best inhibition of lattice contraction was found among 20 pM TC. The best combination was found in the combination of 20 pM TA plus 20 pM TC.Conclusion: The result indicated that a combination of triamcinolone acetonide and tamoxifen citrate had a significant role in suppressing fibroblast activity, better than triamcinolone acetonid or tamoxifen citrate alone.Key words: tamoxifen - triamcinolone - collagen lattice - keloid fibroblast.